Quantum kinetic equations approach to the description of chemical reactions between adparticles at a metallic surface - Ignatyuk, V.V.; Tokarchuk, M.V.; Kostrobij, P.P. (Condensed Matter Physics, 2006)
Adparticle dynamics at a metallic surface is studied by means of quantum kinetic equations. Kinetic equations of the reaction-diffusion type are written down for nonequilibrium one-particle distribution functions of the adsorbate up to the second order in the tunnelling constants and amplitudes of chemical reactions.